Economic analysis of refrigerant blend compared to conventional R-134a based on Power consumption for air conditioning application (Journal of Pharmaceutical Negative Results, 2022)
Aim: This paper presents the power consumption analysis of refrigerants HFO-1234yf , HFC-134a and their blends at differentmass fraction ratios for better performance and cooling capacity.Materials and Methodology: HFO-1234yf is an eco-friendly refrigerant with higher power consumption, HFC-134a is a refrigerant with very good COP and also with high GWP 1430. To overcome this, Tests have been carried out with blending these two refrigerants(X3, X4, X5, X6, X7) and two pure refrigerants (X1, X2) with two different evaporating temperatures (15 C and 30 C). CYCLE_D-HX simulation tool is used to enthalpy and entropy calculations. Thermodynamic analysis has been done to find out Power consumed and Cooling capacity of an air conditioning system. Statistical Packages for the Social Sciences (SPSS) software was used for determining the statistical significance between the two groups. The parameters were maintained as confidential ratio of 95%, threshold 0.01, G power 80% and enrolment ratio as 1. Results and Discussion: Results show that Power consumption at Te=15 C (0.26008 KW) for HFO-1234yf is higher than Te=30c (0.23463KW). There exists a statisticallyinsignificant difference between the two groups (p=0.797; p>0.05). Conclusion:Te=30 C provides less power consumption and moderate cooling capacity than Te= 30C for the selected refrigerants and for the selected mass fraction ratio.